Tarsal tunnel decompression: an effective method for prevention of foot complications in diabetic patients with compressive neuropathy at tarsal tunnel - S., Viswanathan M.; S., Lakshmanan; Anbazhagan, R. (International Surgery Journal, 2018)
Background: Diabetic foot is one of the most devastating complications of diabetes with 15% lifetime risk of developing ulcer foot. About 80% of diabetic foot is neuropathic in origin, revealing the importance of sensory sensation in preventing the development of diabetic ulcer. This study is aimed to identify the efficiency of tarsal tunnel decompression surgery in diabetic patients in ulcer healing and in the prevention of development of new diabetic related foot complications. Methods: About 70 diabetic patients with ulcer in one foot, acting as test limb and contralateral foot having no ulcer, acting as control limb was included in the study. Tarsal tunnel decompression surgery was done in the test limb and the status of ulcer in the test limb, in terms of diameter/ progress of ulcer healing was observed. In both the study limb and the control limb foot was examined for onset of any new diabetes related foot changes/complications during the follow up period for 18 months. Results: Postoperatively, at 6 weeks, 20 patients (28.6%) had their ulcers fully healed. At 3rd month postoperative follow up 90.48% of ulcers in the test limb showed complete healing following decompression surgery and 9.52% of ulcers showed partial healing. Following decompression surgery in the test limb, only 2 patients (3.28%) developed new diabetes related foot changes/complications as compared to control limb, where 15 patients (24.59%) developed new diabetes related foot changes/complications. Conclusions: Present study firmly proves that following tarsal tunnel decompression surgery, there is improvement in healing of the ulcer with conservative measures and there is a definitive role of tarsal tunnel decompression in prevention of development of new diabetes related foot changes/complications in patients.